PENGARUH LEVERAGE, PROFITABILITAS, DAN PERTUMBUHAHAN ASET TERHADAP NILAI PERUSAHAAN - Divna Putri K; Jihan Fijria R; Qoyyimah Nurhakim (Pusat Riset dan Inovasi Nasional, 2022)
In this research, there are several things to aim at, namely to find out how the influence exerted by leverage, profitability and asset growth has on firm value. Quantitative methods used in this study accompanied by data sources in the form of secondary data. The sample used in a company in the processed food industry that is listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period using a purpose sampling method. In this study, 12 sample companies were selected with 36 observation data after being selected according to the provisions of the sample criteria. The model used in data analysis is panel data regression and processed with Eviews 12 software accompanied by several stages of testing. The results obtained from data processing are simultaneously variable leverage, profitability and asset growth have an influence on firm value. However, partially the leverage, profitability and asset growth variables have no effect on firm value.